CTA Annual Report 2010: Building paths to the future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2011)
2010 was particularly important for CTA. We developed a Strategic Plan for the next 5 years, ‘Empowering Rural ACP Communities through Knowledge’. This will ensure that we focus on the critical issues facing agriculture and marshall our efforts through knowledge sharing, networking and capacity building.